2021
DOI: 10.1186/s12870-020-02796-4
|View full text |Cite
|
Sign up to set email alerts
|

Bruchid beetle ovipositioning mediated defense responses in black gram pods

Abstract: Background Black gram [Vigna mungo (L)] seeds are a rich source of digestible protein and dietary fibre, both for human and animal consumption. However, the quality and quantity of the Vigna seeds are severely affected by bruchid beetles during storage. Therefore, analyses of the expression of the bruchid induced transcript dynamics in black gram pods would be helpful to understand the underlying defense mechanism against bruchid oviposition. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…The function of nucleotide metabolism changes due to arthropod oviposition remains as well unclear. Although, it could involve the activation of nucleic acid repair mechanisms or the use of nucleotides as signaling molecules or as metabolic intermediaries (Büchel et al, 2012;Das et al, 2021). An interesting response was found related to cell wall alterations on both species, especially toward later time points.…”
Section: Timeline Of Functional Processesmentioning
confidence: 99%
“…The function of nucleotide metabolism changes due to arthropod oviposition remains as well unclear. Although, it could involve the activation of nucleic acid repair mechanisms or the use of nucleotides as signaling molecules or as metabolic intermediaries (Büchel et al, 2012;Das et al, 2021). An interesting response was found related to cell wall alterations on both species, especially toward later time points.…”
Section: Timeline Of Functional Processesmentioning
confidence: 99%
“…These responses were shown to be dependent on ENHANCED DISEASE SUSCEPTIBILITY 1 (EDS1), ISOCHORISMATE SYN-THASE 1/SALICYLIC ACID INDUCTION DEFICIENT 2 (ICS1/SID2) and, partially, NONEXPRESSER OF PR GENES 1 (NPR1), which are known signaling components of plant defense responses against biotrophic pathogens [26]. Transcriptomic studies in different plants species have confirmed that insect oviposition induces genes associated with SA-and ROS-mediated immune responses and PR1 gene expression [15,24,[27][28][29][30][31][32][33], including in B. nigra and B. rapa [21,34,35]. Further, it has been suggested that there is a conserved transcriptional response amongst different plant-insect egg interactions [36].…”
Section: Introductionmentioning
confidence: 98%
“…It is cultivated throughout Southeast Asia because of its multiple benefits to soil and human health. It is nutritionally important crop with about 25% protein—nearly three times that of cereals, 60% carbohydrates, 1.3% fat ( Das et al, 2021 ) as well as important vitamins and minerals ( Ghafoor et al, 2001 ), making it a balanced vegan diet when supplemented with cereals. The ability of its roots to fix atmospheric nitrogen (42 kg/ha/year) ( Dey et al, 2020 ) contribute towards soil health while deep-roots prevents soil erosion by binding soil particles.…”
Section: Introductionmentioning
confidence: 99%